The Place of Mad People and Disabled People in Canadian Historiography: Surveys, Biographies, and Specialized Fields - Reaume, Geoffrey (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2017)
This article will consider the extent to which mad and disabled people’s histories have, or have not, been included in studies of Canada’s past, including in surveys, biographies and specialized fields. The purpose is to understand when, where and how people deemed mad or disabled have been excluded or included in broader discussions of Canadian history and how the recent growth of mad people’s history and disability history in Canada can influence historiographical developments. There will also be a discussion of how both fields are directly related since people deemed mad were and are to this day categorized under the broad scope of disability, just as are people with physical, sensory and intellectual disabilities. Consideration will also be given to how this field of inter-disciplinary research has benefited from work by researchers who do not necessarily identify as historians in either field but whose work has contributed to these areas, such as through the scholarship of medical historians. The ultimate aim of this paper is to advocate for mad and disabled people’s histories to become incorporated more widely beyond these specialized fields when interpreting Canada’s past.